T cells as a therapeutic target in SLE. (April 2015) - Comte, D; Karampetsou, M P; Tsokos, G C
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease characterized by a loss of tolerance to multiple endogenous antigens. SLE etiology remains largely unknown, despite recent insight into the immunopathogenesis of the disease. T cells are important in the development of the disease by amplifying the immune response and contributing to organ damage. Aberrant signaling, cytokine secretion, and tissue homing displayed by SLE T cells have been extensively studied and the underlying pathogenic molecular mechanisms are starting to be elucidated. T-cell-targeted treatments are being explored in SLE patients. This review is an update on the T-cell abnormalities and related therapeutic options in SLE.